Evaluasi Pengawasan Wajib Pajak Online Marketplace di KPP Pratama Jakarta Pasar Rebo - Sirait, Sandro Torang H.; Abbas, Yulianti (Politeknik Ganesha Medan, 2024)
Recently, people's economic activities have shifted from conventional forms to online forms or what is better known as e-commerce. This is the impact of the rapid development of information and communication technology, especially the internet. People are increasingly interested in shopping online rather than conventionally because shopping online has various advantages, such as: being practical and saving time because you don't need to come directly to the shop to get the goods/services you want, relatively cheaper prices because of the many discounts or promos offered provided, and the quality of the goods is relatively as good as those sold in regular (offline) shops. One form of e-commerce is in the form of online market places, such as: Tokopedia, Shopee, Lazada, and Bukalapak. However, the increase in trader turnover from this online market place was not followed by an increase in tax payments at KPP Pratama Jakarta Pasar Rebo (research location). The Indonesian tax system which implements self-assessment makes tax supervision and audit a tool to increase taxpayer compliance in fulfilling their tax rights and obligations. In this research, the author evaluated tax supervision at KPP Pratama Jakarta Pasar Rebo. Based on theory, there are 5 (five) factors that influence tax supervision, namely: Management Support, Regulations, Account Representatives as tax officers who carry out supervision, Taxpayers, and Information Systems. From the research results, it was found that these factors at KPP Pratama Jakarta Pasar Rebo have been in influencing tax supervision. In this regard, it is necessary to improve the quality of these factors to increase the tax supervision, so that it is hoped that by increasing the tax supervision, taxpayer’s compliance and tax revenues will also increase.